Brand Experience and Brand Trust as Drivers of Customer Satisfaction in the Laundry Service Industry - Rahman, Muhammad Azmi; Yulianti, Ida (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to identify the direct and indirect effects of brand experience and brand trust on the satisfaction of My Klin’s customers. This explanatory study corroborates the causal relationships between its variables through hypothesis testing. Using purposive sampling technique, 75 customers with the minimum age of 17 years who have used the laundry service at least twice in the last six months were selected as the respondents. The research instruments were assessed through validity test, reliability test, and classical assumption test, while the data was analyzed using multiple linear regression and coefficient of determination test, and the hypothesis testing was performed by incorporating the t-test. All of the processes above were conducted in SPSS version 25. This study finds that brand experience partially has a significant effect on customer satisfaction and that brand trust significantly affects customer satisfaction.